Abnormal Respiration and Stress Disorder Monitoring System - Jumain, Nur Adlina; Suriani, Nor Surayahani (Evolution in Electrical and Electronic Engineering, 2021)
The high stress disorder in daily routines may increase the number of sudden death cases. This project aims to study the effect of abnormal respiration rate on the body stress index.  Therefore, this paper purposed to develop a respiration monitoring system detector based on respiration rate and stress index by using temperature sensor (DS18B20), Galvanic Skin Response (GSR) sensor, and pulse sensor. The three variable data collected from 30 subjects by using the sensors were used to evaluate the correlation of abnormal respiration towards body stress index. The program was designed using threshold parameters for three variables data in Arduino IDE to ease the abnormality classification process. The analysis found out that correlation of abnormal respiration towards stress body index is not correlated as in the past research papers. Overall, the respiration system monitoring was designed and successfully validate that abnormal respiration rate leads to body stress detection.